Being green: from attitude to actual consumption. (2nd August 2014) - Miniero, Giulia; Codini, Anna; Bonera, Michelle; Corvi, Elisabetta; Bertoli, Giuseppe
Abstract Interest in issues associated with environmental sustainability is continuously growing and sustainable consumption is now a mainstream topic at the top of the international public administration agenda. However, the many studies about the general inconsistency between green consumer attitudes and green consumption have not considered two individual differences that seem to be interesting in order to explain the ethical consumer attitude–intention gap: regulatory focus and time horizon. Regulatory focus, being the strategic orientation individuals use to pursue their goals, might enhance consumers' sense of duty towards environmental issues. Time horizon represents the consumers' perceived time lag between their decision and its outcome, and can induce them to immediately engage in a specific behaviour. With this goal in mind, the present work illustrates the results of three experimental studies that focus on individual differences (regulatory focus and time horizon) that might influence consumers to comply with green consumption. Results show that prevention‐focused individuals demonstrate a higher compliance with green behaviour, both in the short‐term and in the long‐term outcome horizons.